Kontribusi al-Farabi dalam Bidang Keilmuan - Guntoro, Guntoro (AL-HIKMAH:Jurnal Theosofi dan Peradaban Islam, 2023)
Discourses related to the history of classical Islamic figures, especially the study of the construction of scientific fields and their thoughts, are very complex. This is motivated by the large scientific networks owned by classical Islamic figures who have an influence on the major themes in their work. Al-Farabi was one of the Islamic scientists and philosophers who was very productive in giving birth to various scientific disciplines. So that from various scholars in the following periods various opinions and debates emerged regarding differences in understanding regarding studies, especially those that focus on biographies and works. Al-Farabi experienced a period of growth in unfavorable socio-political conditions, namely living during the second period of the reign of the Abbasids. However, this did not really affect the development of Al-Farabi's knowledge. In his teens he had mastered grammar, literature and religious sciences (fiqh, tafsir, hadith science, basic arithmetic and knowledge of the Koran). The exact chronology of Al-Farabi's work is difficult to determine. He wrote treatises devoted to the explanations of Plato and Aristotle. Al-Farabi also developed his own philosophical thought that united metaphysical and cosmological views with psychology and political philosophy. The existence of Al-Farabi's thoughts is proven by the influence of his thoughts on science and philosophy for several centuries and is widely considered to be the second teacher after Aristotle in the knowledge of his time. Al-Farabi contributed a lot in the field of philosophy and several other scientific disciplines, such as logic, psychology, metaphysics, politics and several other scientific disciplines.Keywords: Socio-Political Conditions, Existence of Thought, Scientific Contributions.